Transplant Glomerulopathy: The Interaction of HLA Antibodies and Endothelium. (9th March 2014) - Hanf, William; Bonder, Claudine S.; Coates, P. Toby H.
Abstract : Transplant glomerulopathy (TG) is a major cause of chronic graft dysfunction without effective therapy. Although the histological definition of TG is well characterized, the pathophysiological pathways leading to TG development are still poorly understood. Electron microscopy suggests an earlier appearance of TG and suggests that endothelial cell injury is the first sign of the disease. The pathogenic role of human leukocyte antigen (HLA) antibodies in endothelial cells has been described in acute vascular and humoral rejection. However the mechanisms and pathways of endothelial cell injury by HLA antibodies remain unclear. Despite the description of different causes of the morphological lesion of TG (hepatitis, thrombotic microangiopathy), the strong link between TG and chronic antibody mediated rejection suggests a major role for HLA antibodies in TG formation. In this review, we describe the effect of classes I or II HLA-antibodies in TG and especially the implication of donor specific antibodies (DSA). We update recent studies about endothelial cells and try to explain the different signals and intracellular pathways involved in the progression of TG.